BIAYA OPERASIONAL, KESESUAIAN TARIF BERPENGARUH TERHADAP KINERJA OPERASIONAL PDAM KABUPATEN BARRU - Astuti, Nur Wafika; Rahim, Syamsu; Hajering, Hajering (AkMen JURNAL ILMIAH, 2024)
Regional Drinking Water Companies (PDAM) are agencies that manage drinking water by regional or city governments. The Regional Drinking Water Company (PDAM) is a Regional Owned Enterprise (BUMD) which has the aim of producing products that comply with the standards of the Ministry of Health, improving the quality and quantity and continuity of a better service so that what the community wants can be fulfilled. This research rigorously aimed to evaluate and assess the extent of the impact of operational costs, suitability of price affects operational performance of PDAM Barru Regency. This study uses a field investigation and is quantitative in nature. This study's population includes all PDAM Barru Regency workers in 2023 and 96 respondents as sample were selected through the Slovin formula, using multiple linear regression analysis. The research results report that operational costs and price suitability have a positive and significant effect on the operational performance of PDAM Barru Regency. These two variables have a significant role in the operational performance of PDAM Barru Regency.